Management of team leadership in extreme context : defending our homeland, protecting our first responders - Graen, George B.; Graen, Joni A. (Emerald Publishing Limited : Information Age Publishing, 2013)
The proper balance of managerial "administrative-control" and managerial "team-leadership" depends upon the work context. After organizational procedures are designed by work-process engineers, managers and their directreports in the business units, are charged to "save our ship" (SOS) by their employers. Their ships, their business units, often were built for calm seas. Unfortunately, turbulent seas may happen unexpectedly and stress their ships and crews. Under extreme conditions, the sea may put their ships squarely in "harm's way". If they are not well prepared, their chances of survival are few and none. This book is about managing and being managed under conditions of "extreme contexts" where only the "special teams" survive and prosper.